Fetal brain 11β-hydroxysteroid dehydrogenase type 2 selectively determines programming of adult depressive-like behaviors and cognitive function, but not anxiety behaviors in male mice. (September 2015) - Wyrwoll, Caitlin; Keith, Marianne; Noble, June; Stevenson, Paula L.; Bombail, Vincent; Crombie, Sandra; Evans, Louise C.; Bailey, Matthew A.; Wood, Emma; Seckl, Jonathan R.; Holmes, Megan C.
Highlights: Aberrant exposures to glucocorticoids during fetal life programme the risk of psychiatric disease in offspring. Placental 11β-HSD2 protects the fetus from maternal glucocorticoids. This study investigates the role of 11β-HSD2 in the fetal brain. Deletion of 11β-HSD2 in the fetal brain causes depressive-like and cognitive dysfunction in adults. Thus fetal brain 11β-HSD2 protects against programming of adult brain function. Summary: Stress or elevated glucocorticoids during sensitive windows of fetal development increase the risk of neuropsychiatric disorders in adult rodents and humans, a phenomenon known as glucocorticoid programming. 11β-Hydroxysteroid dehydrogenase type 2 (11β-HSD2), which catalyses rapid inactivation of glucocorticoids in the placenta, controls access of maternal glucocorticoids to the fetal compartment, placing it in a key position to modulate glucocorticoid programming of behavior. However, the importance of the high expression of 11β-HSD2 within the midgestational fetal brain is unknown. To examine this, a brain-specific knockout of 11β-HSD2 (HSD2BKO) was generated and compared to wild-type littermates. HSD2BKO have markedly diminished fetal brain 11β-HSD2, but intact fetal body and placental 11β-HSD2 and normal fetal and placental growth. Despite normal fetal plasma corticosterone, HSD2BKO exhibit elevated fetal brain corticosterone levels at midgestation. As adults, HSD2BKO show depressive-like behavior and have cognitive impairments. However, unlike complete feto-placental deficiency, HSD2BKO show no anxiety-like behavioral deficits. The clear mechanistic separation of the programmed components of depression and cognition from anxiety implies distinct mechanisms of pathogenesis, affording potential opportunities for stratified interventions.